Changing environment, rising new media: Retesting the exposure-acceptance model in China - Zhehao Liang; You Li (Cogent Social Sciences)
Based on the China data from the World Values Survey (WVS) 2000, Kennedy found a significant curvilinear relationship between education and regime support in the rural subsample but not in the urban subsample, partially verifying the exposure-acceptance model. He attributed this phenomenon to the “urban–rural gap” in educational opportunities in China. In the past two decades, China has narrowed this gap. Has this changed the patterns of regime support? To revisit this question, we replicate Kennedy’s analyses using the WVS 2018 data. The results fail to support the exposure-acceptance model in either the rural or the urban subsample. This inconsistency may stem from the explosive growth of new media in China over the past 20 years, which has made criticism more accessible. New media can affect people’s media exposure patterns in a way that goes beyond the scope of the exposure-acceptance model. Therefore, we introduce the measure of new media usage into Kennedy’s models and find a linear negative effect on regime support at the national level. We conclude that the applicability of the exposure-acceptance model may have declined in China due to the rise of new media. The long-term influence of new media on regime support in authoritarian nations should be explored in further research.